2019
DOI: 10.1021/acs.iecr.9b00420
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Promotional Effects of K, Sr, and Mg on the Catalytic Stability of Red Mud for the Synthesis of Glycerol Carbonate from Renewable Glycerol

Abstract: The focus of this study was to utilize red mud (RM), an aluminum industry waste, for the preparation of various catalysts for the synthesis of glycerol carbonate (GC) from glycerol (GL). A series of catalysts were prepared by doping potassium, strontium, and magnesium on the surface of RM, and their effect on the stability of RM based catalysts was examined. From preliminary studies, K-doped RM catalysts were found to have better activity as well as stability than the Sr-and Mg-doped RM catalysts for the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Layered double hydroxides have also been widely reported for the reaction [27][28][29] . Catalysts for the reaction can also be prepared from a variety of waste sources such as oil palm ash 30 , steel slag 27,31 and red mud 32,33 .…”
Section: Figure 1 -Reaction Scheme For Synthesis Of Glycerol Carbonat...mentioning
confidence: 99%
“…Layered double hydroxides have also been widely reported for the reaction [27][28][29] . Catalysts for the reaction can also be prepared from a variety of waste sources such as oil palm ash 30 , steel slag 27,31 and red mud 32,33 .…”
Section: Figure 1 -Reaction Scheme For Synthesis Of Glycerol Carbonat...mentioning
confidence: 99%
“…Likewise, evaluation of the impact of K, Sr, and Mg on the catalytic stability of red mud in GC synthesis revealed that a 30 wt% K loading and calcination at 800 °C resulted in the most favorable catalytic performance due to the maximal surface concentration of active K 2 O. 28 The synthesis process of glycerol carbonate is known for its high energy consumption and signicant costs, necessitating optimization through the application of appropriate statistical tools. Specically, the identication of optimal reaction parameters to maximize glycerol carbonate yield is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst's surface contains basic sites responsible for initiating the transesterification process. Catalysts functionalized with metals, such as potassium (K), 28,29 sodium (Na), 30 Li, 6,29 magnesium (Mg), 28,29 strontium (Sr), 28 and zirconium, 22 exhibit an enhanced performance in GC production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to catalytic performance, separation efficiency, and environmental friendliness, the cost of the catalyst preparation is also a key factor that should be considered. Ionic liquids [34,35] and biological enzymes [36,37] as new green catalysts have attracted great attention. However, the complex preparation process and relatively high preparation cost seriously limit the application of these catalysts in the industrial field.…”
Section: Introductionmentioning
confidence: 99%